Trade-Offs between Risks and Returns of Multiple Vegetable Cropping Systems - Mohamed, Zainal Abidin; Thani, Pichit (Universiti Putra Malaysia Press, 1993)
Production of crops as a business venture is considered risky. A farmer faces variations in prices, yield and resource constraints that make income unstable. This study looks at the trade-off between farm returns (E) and risk (V) (as measured by variance of expected income) in a vegetable crop diversification programme. The study demonstrates how minimum risk farm plans can be estimated to allocate available land to match the vegetable crop combinations efficiently in situations of risk and uncertainty. The E-V frontier is traced to evaluate the trade-offs between risks and returns of each combination of the vegetable crops. The results indicate that farmers with high risk aversion i.e. at the lower E-V frontier should plant more "ladies fingers" spinach and cucumber, while farmers who are risk neutral i.e. at the higher E-V frontier should plant more high risk crops such as bitter gourd and "kailan".